A REVIEW STUDY ON THE IMPACT OF SPIRITUAL INTELLIGENCE ON DIETARY CHOICES AND NUTRITIONAL WELL-BEING IN ADOLESCENTS OF THE 21ST CENTURY (International Journal of Food and Nutritional Sciences, 2022)
Till the early 21st century it was believed that only rational intelligence i.e. IQ has a role in the success of an individual’s life. Later, the research added the importance of emotional intelligence i.e EQ to the success of an individual too. It is only during the middle of the 21st century, that the researchers found about spiritual intelligence or the spiritual quotient i.e. SQ, and emphasized its importance at every stage of growth and development of the individual.Spiritual Intelligence is the wisdom and compassion that individual displays in every situation and at the same time maintaining inner and outer peace. IQ, EQ, and SQ all three play a major role in creating a quality life for an individual.